Sexually Transmitted Diseases: from HPV to HTLV - clinical profile and associated factors - Fabíola Suris da Silveira; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2015)
Abstract: The Brazilian Ministry of Health recommends the performance of serological tests in patients with clinical signs of Sexually Transmitted Diseases. However, data are lacking to affirm the necessity of testing these patients for human T-lymphotropic virus type 1 or type 2. This is a cross-sectional study with 120 patients seen at the Sexually Transmitted Diseases unit of the Sanitary Dermatology Outpatient Clinic of Rio Grande do Sul. The serum from none of the patients was positive for human T-lymphotropic virus type 1 or type 2. Viral warts were the most frequent diagnosis. Drug use was confirmed as a risk factor and high educational levels were found to be a protective factor against Sexually Transmitted Diseases.